ELEMENTS OF TRADE SECRETS MANAGEMENT FOR INNOVATION - Rossi, Juliano Scherner (2018)
This paper proposes corporate policies for the protection and transfer of knowledge and collaborative innovation with an emphasis on technological know-how, and reports on certain shortcomings in existing legal frameworks for the protection of trade secrets. It presents a theoretical framework of knowledge management that incorporates trade secrets protection processes into companies’ routines. Companies should develop a risk management policy with respect to trade secret and integrate it into the company's code of conduct. Convergence of trade secret law between jurisdictions increases legal certainty to prevent more effectively theft. This survey adopts the monographic method and an inductive approach. The focus is not on results but rather on theoretical models that address the issue.